Updated number forecast, russian car fleet structures by type of power plants and greenhouse gas emissions until 2050 - IU. V. Trofimenko; V. I. Komkov (Вестник СибАДИ, 2023)
Introduction. The results of forecast estimation of the number, structure of the Russian motor vehicle fleet by type of power units and greenhouse gas (GHG) emissions up to 2050 are presented, taking into account the update of the initial data used in the calculations and the assumption that it will be decided to stop production of passenger cars with internal combustion engines starting from 2045. Materials and methods. The forecast of the level of motorization, the number of vehicle fleet by type of power plant and fuel type, environmental class were estimated taking into account the renewal of the fleet, the balance of supply and disposal of ATVs. These data are given in the forms of state statistical reporting, long-term strategies of transport industry development, partly generated by researchers themselves. The Copert 5 methodology was also used to calculate greenhouse gas emissions.Results. Compared to earlier projections, the value of total GHG emissions of the vehicle fleet in 2050 according to the current projection will be about the same as in 2045, i.e. will be 5 years behind. Discussion and conclusions. In the near term, the rate of decarbonization of road transport in Russia may slow down significantly. Vehicles with internal combustion engines using hydrocarbon fuels (liquid, gaseous) will still dominate the vehicle fleet by 2050.